Investigations on the liver function and its prognostic value in dairy cows with hypocalcaemic paralysis - PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ), N.; ROUBLES (Ν. ΡΟΥΜΠΙΕΣ), N.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ), H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Investigations on the liver function and its prognostic value were performed in dairy cows with hypocalcaemic paralysis. Among the 107 animals affected by milk fever 22 showed signs of liver insufficiency. In spite of the therapy indicated, 7 of these animals were not cured. The remaining 85 sick cows, which had showed a physiologic liver function, were cured after the first therapy was applied.